Design Of A Stock Management Information System Using The First In First Out (FIFO) Method In One Of The MSMEs In Bandung - Muhamad Rizki; Dheni Apriantsani Budiman; Ade Supriatna; Eko Retnaldi (Informatics Management, Engineering and Information System Journal, 2025)
The stock management process is essential for SMEs, as one SME in Bandung employs a manual approach that often requires considerable time and data collection.  The swift progression of technology facilitates the presentation of information with ease, speed, and efficiency.  Manual stock management can be converted into a computerised system referred to as stock management information systems.  A technology-driven stock management system will enhance efficiency by supplanting the manual system with a systematic approach.  This project aims to analyze and develop a web-based stock management information system suitable for a small to medium-sized enterprise in Bandung. The research conducted is descriptive and utilises a qualitative methodology.  The inventory management approach employed is FIFO (First In First Out), whereas the system development methodology adheres to the Waterfall SDLC model.  Flowcharts, entity relationship diagrams, and data flow diagrams underpin the design.  This stock management system is constructed with PHP as the programming language, Visual Studio Code as the code editor, XAMPP as the web server, and MySQL as the database.  The implementation of the FIFO approach in inventory management is expected to resolve problems associated with dim sum being stored for extended periods in the warehouse, resulting from the prior flow of items, thereby enhancing the accuracy and efficiency of stock management.  This research should be further developed into a mobile application to provide user access via cellphones.